2D Materials: Designing the Bending Stiffness of 2D Material Heterostructures (Adv. Mater. 9/2021). Issue 9 (2nd March 2021) - Yu, Jaehyung; Han, Edmund; Hossain, M. Abir; Watanabe, Kenji; Taniguchi, Takashi; Ertekin, Elif; van der Zande, Arend M.; Huang, Pinshane Y.
Abstract : A single graphene sheet is stacked on top of monolayer MoS2 . The 2D heterostructure is buckled out‐of‐plane, inducing bending in both layers. In article number 2007269, Arend M. van der Zande, Pinshane Y. Huang, and co‐workers study the impact of interfacial engineering on the tunability of the bending stiffness in 2D multilayers. A bending model is developed to predict and design the deformability of any arbitrary 2D heterostructure.